Performance analysis of two typical greenhouse lettuce production systems: commercial hydroponic production and traditional soil cultivation - Wang, Lichun; Ning, Songrui; Zheng, Wengang; Guo, Jingyu; Li, Youli; Li, Yinkun; Chen, Xiaoli; Ben-Gal, Alon; Wei, Xiaoming (Frontiers in Plant Science, 2023)
Due to the shortage of land and water resource, optimization of systems for production in commercial greenhouses is essential for sustainable vegetable supply. The performance of lettuce productivity and economic benefit in greenhouses using a soil-based system (SBS) and a hydroponic production system (HPS) were compared in this study. Experiments were conducted in two identical greenhouses over two growth cycles (G1 and G2). Three treatments of irrigation volumes (S1, S2 and S3) were evaluated for SBS while three treatments of nutrient solution concentration (H1, H2 and H3) were evaluated for HPS, the optimal levels from each system were then compared. HPS was more sensitive to the effects of environmental temperature than SBS because of higher soil buffer capacity. Compared with SBS, higher yield (more than 134%) and water productivity (more than 50%) was observed in HPS. we detected significant increases in of ascorbic acid by 28.31% and 16.67%, soluble sugar by 57.84% and 32.23 during G1 and G2, respectively, compared with SBS. However, nitrate accumulated in HPS grown lettuce. When the nutrient solution was replaced with fresh water 3 d before harvest, the excess nitrate content of harvested lettuce in HPS was removed. The initial investment and total operating cost in HPS were 21.76 times and 47.09% higher than that in SBS, respectively. Consideration of agronomic, quality and economic indicators showed an overall optimal performance of the H2 treatment. These findings indicated that, in spite of its higher initial investment and requirement of advanced technology and management, HPS was more profitable than SBS for commercial lettuce production.